PERCEIVED ACCESS TO FINANCE, SELF-EFFICACY, AND ATTITUDE ON STUDENT’S ENTREPRENEURIAL ABILITY AND INTENTION - Gianeta Gianeta; Chrisanty V. Layman (Milestone: Journal of Strategic Management, 2023)
This study aims to analyze the influence of perceived access to finance, self-efficacy, and attitude toward entrepreneurship directly on the entrepreneurial intention and indirectly through entrepreneurial ability. The subjects of this study are 190 respondents who are undergraduate students from various majors who had studied for at least one year at Pelita Harapan University. The study uses quantitative research by taking samples using a purposive sampling technique. Data analysis was performed by Partial Least Square-Structural Equation Modelling (PLS-SEM) using the software SmartPLS 3.2.9. The results of this study indicate that perceived access to finance, self-efficacy, and attitude toward entrepreneurship has a positive on entrepreneurial ability. Meanwhile perceived access to finance is not significant to entrepreneurial intention, however self-efficacy and attitude toward entrepreneurship have a positive influence on entrepreneurial intention. Furthermore, the study found that entrepreneurial ability mediates those influences towards entrepreneurial intention. The study showcases the important mediating effect of entrepreneurial ability towards entrepreneurial intention. This supports universities to build on more practical business capabilities of their students to encourage them to start businesses.